Who Participates in Building Disaster Resilient Communities: A Cluster-Analytic Approach. Issue 1 (January 2017) - Adams, Rachel M.; Rivard, Helene; Eisenman, David P.
Abstract : Context: The Los Angeles County Community Disaster Resilience project is a community-based program to improve disaster resilience. We collected baseline measures of resilience-related attitudes and practices among targeted communities prior to the implementation of the intervention. Objectives: This study identified community disaster resilience behavior patterns and assessed their associations with sociodemographic and social cognitive characteristics. Design: Telephone surveys during summer 2013. Setting: Sixteen communities in Los Angeles County (2 per service planning area). Participants: The address-based sample of adults (≥18) was selected to be representative of 2010 census tracts in each of the communities Main Outcome Measures: We examined relationships between sociodemographic characteristics, social cognitive factors, and participation in community disaster resilience activities. Results: Three clusters of community resilience behavior patterns emerged. Cluster distribution significantly differed across several sociodemographic and social cognitive factors. Participants who were African American, Hispanic, had higher education, income, self-efficacy, trust in the public health department, civic engagement, and social capital were significantly associated with being in the cluster most active in resilience-building activities. Conclusions: The results confirm that there are distinct community resilience behavior patterns. These patterns vary according to population characteristics, which supports audience segmentation approaches and developing a range of emergency preparedness programs targeted to the strengths and weaknesses of the different audience segments. Abstract : Supplemental Digital Content is Available in the Text.